A new strategy to strongly release sweet-enhancing volatiles from goji pomace using trivalent iron salts. (May 2023) - Han, Xue; Zhang, Na; Luo, Lingxi; Zhang, Yanyan; Wang, Mengze; Yin, Xiaoyu; Zhang, Bo; Fan, Junfeng
Graphical abstract: Highlights: We first use FeCl3 to fully release the volatile compounds from plant resources. FeCl3 strongly releases the sweet-enhancing volatiles (SVs) from fruit pomace. FeCl3 acts as Brønsted and Lewis acids to hydrolyze and release the bounded SVs. FeCl3 degrades β-carotene and β-ionone to SVs via the oxidation of iron radicals. SVs can be concentrated into sweet essence to substitute sugar intake. Abstract: Efforts to fully utilize pomace volatiles have been obstructed by the lack of high-performance technologies to release free and bound volatiles. This study first established that ferric chloride (FeCl3 ) could strongly release the sweet-enhancing volatiles (SVs) from goji pomace, thus increasing the main aroma compounds [MACs; odor activity value (OAV) > 1] from 9 to 27. The underlying mechanism included the special hydrolysis to glycosides by ferric ions acting as Brønsted and Lewis acids, and the oxidation of β-carotene and β-ionone by electrophilic ferrite. The sweet fragrance could be reconstituted and simulated by the 27 MACs. Subsequent extraction and concentration increased MACs on average by 2.28-fold, and the extracted essence could be used as a green and safe sweet-enhancing sugar substitute for specific consumers. These study findings laid a foundation for understanding the relationship between metal salts and flavor chemistry, further providing an opportunity for the full utilization of resources.